Multiply 2x-5y= -21 by 3 to make it 6x-15y= -63
Multiply 3x-3y= -18 by -5 to make it -15x+15y=90
This cancels the y’s out which leaves us with
6x=-63
&
-15x=90
x for 6x=-63 equals - 10.5 so x is - 10.5 and for -15x=90, x= -6
Then you plug in x into any equation you’d like to find y.
Let’s plug in - 10.5 into 6x... equation.
6(- 10.5)-15y=-63
63-15y= -63
-63 -63
-15y=0
y=0 and x= - 10.5. When you plug in this values it makes the equation true!
But the correct answer is the first one north. Sorry if I’m doing too much hahah
If I’m confusing here’s the right answer...
6x-15y= -63
-15x+15y=90
Answer: First Option | 2 x 10^1
Reason: After doing 6.4 divided by 3.2, you get 2, and finally you subtract 10³ by 10². And after that subtraction, you get 10^1, Therefore the answer is the first option.
<em>I hope this helps, and Happy Holidays! :)</em>
Answer:
Answer: x = a*y + 3
Step-by-step explanation:
To make x the subject of the equation, first, we open the bracket
4x - 12/a = y
Then cross multiply:
4x - 12 = a * y ( a*y means the product of the two variables)
Add 12 to both sides of the equation
4x = a*y + 12
Divide both sides by 4 to get the value of x
x = a * y + 12/4
x = a*y + 3
The answer to this question is 25.